Antagonismo a Macrophomina phaseolina e promoção do crescimento em feijoeiro mediados por Trichoderma spp. - Broetto, Laline (2013)
Charcoal rot caused by Macrophomina phaseolina is a disease that occurs in a large number of plant species and besides not being economically controlled by fungicides, no genetic resistance has been found. On the other hand, there is a growing awareness of the proper handling of pesticides or of the search for new and environmentally safer technologies for handling of plant diseases. Therefore this study aimed to select isolates of Trichoderma sp. for biological control of M. phaseolina and to evaluate their mechanisms of antagonism, as well as its effect as growth promoter of common bean. Seventeen isolates of Trichoderma sp. were used, in two in vitro tests: direct confrontation with the pathogen and production of volatile compounds. After the in vitro tests, six isolates that showed increased aggressiveness to the pathogen were selected and tested in vivo for effectiveness in controlling M. phaseolina and capacity of promoting common bean growth. The isolates TI1, TM3, TM4, TLB2, TLB3, TLB9, TLB15 and TLB17 showed antagonism against M. phaseolina in direct confrontation, and the isolates TM2, TLB2, TLB12, TLB15 and TLB17 reduced the mycelial growth of the pathogen in the volatile compounds test. Regarding microsclerotia of the pathogen, all the isolates were capable of reducing their production. The isolates TI1, TM3, TLB3, TLB12 and TLB17 were good growth promoters of common bean and the isolates TI1, TM3, TLB2, TLB3, TLB12 and TLB17 increased production per plant, especially the isolate TLB12. Regarding the protection of common bean against M. phaseolina, the isolates TLB2, TLB3, TLB12 and TLB17 were efficient. Fungi of the genus Trichoderma show effectiveness in controlling M. phaseolina and stimulate growth and increase the production of common bean